Wielkie figury semantyczne w dziele filmowym - HENDRYKOWSKI, MAREK (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Great semantic figures in film This study is devoted to the key issue for any research on film, film art and audiovisual communication - great semantic figures. Marek Hendrykowski extrapolates the repertoire of basic concepts developed for decades in literary science (author, reader, narrator, narration, character, time, space, events, plot, style, composition, etc.) into academic film studies. Following important scientific ideas formulated half a century ago by the eminent literary theorist Janusz Slawinski, Hendrykowski stresses that the scientific sense of using these categories is not limited only to cataloguing them.